Kemampuan Mahasiswa Menganalisis Tes (Soal) Bahasa Indonesia Sesuai Aspek Ranah Kognitif Model Anderson dan Krathwohl - Yulistio, Didi (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
The purpose of this study was to describe the ability to analyze the Indonesian language test (question) made by Indonesian language teachers according to the cognitive domain of the Anderson and Krathwohl model online for students of the Indonesian Language Education S-1 Program FKIP Bengkulu University, regarding the construction of (a) the characteristics of the cognitive domain according to the verb operational, (b) interesting and contextual-based question stimulus, and (c) Indonesian language question construction applying KKO. This study uses a descriptive method and a simple quantitative approach as well as through an online learning system. Data collection uses documentation and test techniques. The research instrument was in the form of document recording guidelines (tests) to analyze all teacher-made Indonesian questions to obtain a description of the quality of each question. The research data is in the form of 40 documents resulting from descriptions of Indonesian language questions (essays and multiple choice) which cover six cognitive aspects. The main data analysis technique uses the average formula and qualitative conclusion analysis through the description of the construction of Indonesian language questions. Based on the results of the study, it was found that the ability of students to analyze teacher-made Indonesian tests (questions) in online lesson plans based on the cognitive domain of the Anderson and Krathwohl model online for undergraduate students of Indonesian Language Education FKIP Bengkulu University was categorized as good with an average score of 89.25 (at score range 73-96). These results are corroborated by the average score of the six cognitive aspects of 7.44 in the good category (in the score range 7-8). Students have been able to analyze the use of operational verbs in the six cognitive aspects in the construction of essay and multiplechoice Indonesian test kits (questions). A description of the use of operational verbs in Indonesian language questions explicitly or implicitly, such as the use of the word explaining in the aspect of knowing (C1), the word mentioning the characteristics in the aspect of understanding (C2), the word determining in the aspect of applying (3), the word finding meaning in the aspect of analyzing (C4), the word concludes the content of the text on the evaluating aspect (c5), and the word develops or writes a short story on the creative aspect (C6).